Ketidaksadaran M. Aan Mansyur sebagai penyair dalam puisi Kata Membutuhkan Rahasia - Rusman, Wafa Nabila; Wirajaya, Asep Yudha (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2024)
Poetry is the recording and interpretation of important human experiences transformed into beautiful and memorable language forms so that poetry can be used to study the expression of the poet's soul. This research focuses on finding M. Aan Mansyur's unconscious as expressed in his poem, Kata Membutuhkan Rahasia. This research begins by tracing M. Aan Mansyur's psychobiography and then connecting it with the linguistic data in the poem, which is analyzed using Sigmund Freud's dream interpretation theory. The poet's unconsciousness contained in the poem is shown through linguistic symbols, namely condensation, diversion, and symbolization. M. Aan Mansyur is a person who learns from experience and does not let others experience the same bad experience. This character is expressed in the poem, which conveys the importance of being careful when speaking. The poet's experience as a victim of verbal bullying in the past provides its perspective for the creation of this poem.